Legal and Political Policy in Preventing of Money Politics: Case Study and Recommendations - Siddiq, Achmad; Hariyanto (Indonesian Academy of Social and Religious Research (IASRR), 2024)
Money politics has damaged the democratic system throughout the nation; handling the problem of money politics is not enough to be charged to law enforcement and all elements of society. The seriousness of the government and political parties in tackling the problem of money politics can be done by legal and political means. The results of this study show that political policies in preventing money politics in the 2019 elections in Banyumas Regency where political parties have made several efforts in at least three ways: 1) implementing pacta integrity and providing debriefing to cadres and legislative candidates. 2) All parties tend to follow only the existing rules, especially those issued by the KPU and Bawaslu. 3) It turns out that all parties do not require this, relating to the competency requirements of legislative candidates that are more stringent, intellectual, managerial skills, experience, and morality. Legal policies in the prevention and handling of money politics have carried out prevention strategies through legal policies, namely prevention at the level of legislation policy and judicial policy. In contrast, the execution policy has yet to be well realized.